THE STYLISTIC FEATURES OF THE DESIGN OF POSTERS OF THE XI'AN FILM STUDIO - YANG, YI; DUBRIVNA, A. (Art and Design, 2024)
Purpose of the study is to clarify the artistic features, style characteristics, and existing flaws in the poster design of different genre films produced by Xi'an Film Studio at different stages of its development, through the analysis of a large number of historical posters from Xi'an Film Studio; the use and development of graphics, colors, and symbols in the poster design; the exploration of the influence of the aesthetics of Western cinema. Methodology is based on the system-analytical, comparative, figurative-stylistic, compositional- constructive, comprehensive-historical and semiotic methods. This made it possible to comprehensively investigate the specified problem, made generalization and reach reasonable conclusions. Results. The main features of Xi'an Film Studio's movie poster design are revealed. The main characteristics of the design, existing flaws, and the application of the poster design of Xi'an Film Studio are summarized. According to the results of the research, the use and development of graphics, colors, and symbols in the poster design of Western cinema are summarized and applied. Scientific novelty. The characteristics and the application of Xi'an Film Studio's movie poster design are analyzed, the regional symbols that are applicated in the design are revealed, and some practical results and solution of Xi'an Film Studio's movie poster design are summarized. Moreover, an perspective that integrates media convergence and interdisciplinary approaches, combining theories from semiotics and communication studies to analyze various dimensions of poster design at the Xi'an Film Studio are be developed. A substantial amount of primary visual and textual materials has been gathered to facilitate a comprehensive analysis. Practical significance. The results of the study can be used to analyze and develop the application of design principles in the poster designs, brand designs, digital media and interactive design, provide practical experience for incorporating cultural elements into design, and offer a pathway for designing local cultural products in Shaanxi.